Immune Senescence Factors Associated with the Immunogenicity of a Live Attenuated Zoster Vaccine (ZV) in Older Adults. (4th October 2017) - Weinberg, Adriana; Schamder, Kenneth; Johnson, Michael; Popmihajlov, Zoran; Tovar-Salazar, Adriana; Caldas, Yupanqui; Pang, Lei; Cho, Alice; Levin, Myron
Abstract: Background: ZV confers protection against herpes zoster by increasing the cell-mediated immunity (CMI) to varicella-zoster virus (VZV). ZV immunogenicity and protection decrease with increasing age. We investigated effects of age and immune senescence on ZV immunogenicity. Methods: 399 adults ≥50 years had VZV T-cell helper 1 (Th1) CMI measured by ex vivo VZV-stimulated IL2/IFNg ELISPOT and blood T-cell nonspecific immune senescence by flow cytometric characterization of FOXP3, CD25, IL10, TGFb, PD1, CD28, CD57 and CD31 expression before and at 1, 6 and 52 weeks after ZV. In a subset of 95 vaccinees, VZV-stimulated T cell expression of CD107, Granzyme B, FOXP3, CD25, IL10, TGFb, CD39 and PD1 were also measured. Multivariate regression analysis was used to identify independent effects of age and immune senescence on VZV Th1 CMI ( P < 0.025). Results: IL2+ and IL2+IFNg+ Th1 memory VZV CMI peaked at 6 weeks after ZV and remained elevated at 1 year. Effectors, including VZV-specific IFNg+ Th1, and CD8+CD107+% and CD4+/CD8+Granzyme B+% cytotoxic T lymphocytes (CTL), peaked at 1 week, but only the IFNg+ Th1 effectors remained elevated at 1 year. There was also a transient increase in blood CD8+PD1+% exhausted T cells 1 week after ZV. Independent positive effects on peak memory Th1 VZV CMI included the baseline CMI and negative effects included blood CD4+FOXP3+% T regulatory (Treg) and CD8+PD1+% T exhausted cells. Independent positive effects on peak effector Th1 VZV CMI included baseline CMI and negative effects included blood CD8+CD25+FOXP3+% Treg. Age did not have an independent effect on peak CMI. Independent positive effects on persistent (1 year) memory Th1 included baseline CMI and negative effects included age, blood CD4+FOXP3+% Treg and CD8+PD1+% T exhausted cells. Persistent effector Th1 CMI was negatively affected by age only. Conclusion: ZV generated VZV-specific Th1 and CTL responses. The early increase of CD8+ exhausted T cells in blood suggested that CTL responses to the vaccine virus may be compromised by immune senescence. The negative of age on VZV Th1 CMI was fully mediated by immune senescence at peak response, but age had a negative effect on CMI persistence that was independent from the markers of immune senescence included in this study. Disclosures: A. Weinberg, merck: Grant Investigator, Research grant K. Schamder, merck: Grant Investigator, Research grant Z. Popmihajlov, Merck & Co., Inc.: Employee and Shareholder, Salary L. Pang, Merck: Employee and Shareholder, Salary M. Levin, merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant